2018
DOI: 10.5114/ms.2018.76869
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of relaxation therapy on decreasing anxiety in patients with elective caesarean section in Imam Khomeini Hospital, Ahvaz, Iran during 2016

Abstract: Introduction: Caesarean section, due to delivery and operating room and anaesthesia as well as well-known complications for the patient, can cause anxiety in patients, and this anxiety creates physical problems for the patient. Aim of the research: To investigate the effects of relaxation therapy on decreasing anxiety in patients with elective caesarean section. Material and methods: This clinical trial was conducted on 90 pregnant women (45 persons in each of two groups), aged 20 to 35 years old, who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Regarding post-caesarean section anxiety, with similar conditions, this technique can be a therapeutic option to reduce implicit anxiety and total anxiety in women. 12 Masoumeh's research is supported by Donsu's research which suggests that relaxation performed with meditation and deep breathing techniques can be used to activate sympathetic nerves. so that it can be used to overcome psychological problems such as stress, anxiety, pain and depression.…”
Section: Discussionmentioning
confidence: 94%
“…Regarding post-caesarean section anxiety, with similar conditions, this technique can be a therapeutic option to reduce implicit anxiety and total anxiety in women. 12 Masoumeh's research is supported by Donsu's research which suggests that relaxation performed with meditation and deep breathing techniques can be used to activate sympathetic nerves. so that it can be used to overcome psychological problems such as stress, anxiety, pain and depression.…”
Section: Discussionmentioning
confidence: 94%
“…Nazarinasab et al suggested a muscle relaxation therapy technique in patients with elective caesarean section as a method to decrease anxiety [26].…”
Section: Methodsmentioning
confidence: 99%